Strategic Approaches in Developing Competent Students in Traditional Islamic Boarding Schools - Azizah, Balkis; Izzati, Nurul; Aprilia, Fina Triana (IJIBS, 2024)
The sustained existence and growth of Islamic boarding schools in Indonesia highlight their resilience and relevance, attributed to their unwavering mission, vision, and effective learning methodologies. Despite being considered traditional, methods like bandongan and sorogan have proven successful in producing capable students, reflecting their effectiveness. Previous studies have explored these methods but lack a focused evaluation of the factors influencing their implementation and outcomes. Addressing this gap, this study investigates the supporting and inhibiting factors that shape the learning process using these methods at Darul Huda Jugang Melis Islamic Boarding School, Trenggalek. This qualitative field study employs a descriptive approach, involving ustadz, caregivers, and students as subjects. Data collection methods include observations, interviews, and documentation, followed by thematic analysis. The findings reveal three supporting factors: positive perceptions of the methods, well-qualified teachers, and adequate facilities. Conversely, three inhibiting factors include the absence of age limits among students, inadequate preparation of learners, and insufficient support from guardians. This research underscores the importance of balancing traditional methods with contextual challenges to optimize learning outcomes. It contributes to the discourse on traditional educational practices, offering insights for improving the application of bandongan and sorogan methods in modern contexts.